PIC simulation of nonlinear wakefield excitation by a train of electron bunches in a waveguide with isotropic plasma - Markov, P.I.; Onishchenko, I.N.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2008)
The results of analytical investigations and numerical simulation (in 2.5–dimensional electromagnetic code) of nonlinear wake fields excitation by regular sequence of relativistic electron bunches in isotropic (no external magnetic field) plasma are presented. The dynamics and distribution of electromagnetic field are investigated. The waves predicted in the system by linear theory of wake fields excitation were observed in the numerical experiment.